Enabling Organizational Resilience Amidst Disasters: Experiences of Work Organizations in Southeast Asia - Teng-Calleja, Mendiola (Archīum Ateneo, 2020)
This chapter describes the environmental risks and vulnerabilities faced by work organizations in Southeast Asia. It also presents cases that demonstrate how these organizations respond to disasters and natural hazards. To situate the case discussions, a review of existing studies of organizational resilience, particularly those that propose definitions, models, and frameworks is presented. The cases from the Philippines and Thailand illustrate how active and integrative efforts at building resilience can be institutionalized at the organizational level.